EFL Students’ Perception on Online Peer Feedback in Improving Their Academic English Writing Ability - Dodi Settiawan (Nalar Global, 2021)
The study aims to examine the perception of university students on the implementation of online peer feedback and to explore their patterns of interaction on online peer feedback in academic English writing. The study employed the embedded model of a mixed-methods research of which a qualitative strand was embedded in a quantitative analysis to reinforce the research design. The findings reported that the mean scores of the students’ perception on online peer feedback were positive after the implementation of online peer feedback training. The findings of written-reflections can be classified in four emerged themes. The themes include the writing and online peer-feedback process, developed their affective strategy, raised their critical thinking abilities, and their beliefs and changes for writing ability improvement. The findings of the study corresponded to each research question. Therefore, online peer feedback should be taken into consideration in academic writing class.